2000
DOI: 10.1002/1522-726x(200008)50:4<498::aid-ccd28>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The use of intrastent peripheral stent in large coronary arteries: Report of three cases

Abstract: We report three cases of coronary angioplasty using the IntraTherapeutics Intrastent biliary stent. We describe a technique utilizing routine coronary angioplasty equipment including 8 Fr guiding catheters and 0.014" guidewires. This technique can be easily performed in large-diameter coronary arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Agirbasli et al reported 3 cases of coronary angioplasty with intra-therapeutic peripheral biliary stents for CAE 8. This was the first report of using a peripheral biliary stent in a coronary vascular structure.…”
Section: Discussionmentioning
confidence: 99%
“…Agirbasli et al reported 3 cases of coronary angioplasty with intra-therapeutic peripheral biliary stents for CAE 8. This was the first report of using a peripheral biliary stent in a coronary vascular structure.…”
Section: Discussionmentioning
confidence: 99%
“…Case series of older generation biliary stents showed the feasibility but were associated with higher rates of in stent restenosis up to 12%. . In general, there is an inverse relationship between diameter of the stents and post procedural complications and late in stent restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…We had no MACE to report after a follow up period of over two years. Case series of older generation biliary stents showed the feasibility but were associated with higher rates of in stent restenosis up to 12%.. 10,11 In general, there is an inverse relationship between diameter of the stents and post procedural complications and late in stent restenosis. It has been shown that MACE rates especially those related to in stent restenosis are lower in large diameter arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous venous graftcovered stent is a valuable approach in selected cases to seal the coronary artery aneurysm (111). Biliary, sirulimus-eluting, and recently carotid stents have been used to intervene on the stenotic ectatic coronary arteries (112)(113)(114). However, there are no evidence-based guidelines for the management of stenotic lesions associated with CAE.…”
Section: Role Of Revascularizationmentioning
confidence: 99%